Thoughts of suicide or self-harm among Australian healthcare workers during the COVID-19 pandemic. (December 2022) - Bismark, Marie; Scurrah, Katrina; Pascoe, Amy; Willis, Karen; Jain, Ria; Smallwood, Natasha
Objective: To identify the prevalence and predictors of (a) thoughts of suicide or self-harm among healthcare workers during the COVID-19 pandemic and (b) help-seeking among those healthcare workers with thoughts of suicide or self-harm. Method: Analysis of data from the Australian COVID-19 Frontline Healthcare Workers Study, an online survey of healthcare workers conducted during the second wave of the COVID-19 pandemic in Australia. Outcomes of interest were thoughts of suicide or self-harm as measured through the Patient Health Questionnaire for depression and help-seeking behaviours. Results: Overall, 819 (10.5%) of 7795 healthcare workers reported thoughts of suicide or self-harm over a 2-week period. Healthcare workers with these thoughts experienced higher rates of depression, anxiety, post-traumatic stress disorder and burnout than their peers. In multivariable models, the odds of suicide or self-harm thoughts were higher among workers who had friends or family infected with COVID-19 (odds ratio = 1.24, 95% confidence interval = [1.06, 1.47]), were living alone (odds ratio = 1.32, 95% confidence interval = [1.06, 1.64]), younger (⩽30 years cf. >50 years; odds ratio = 1.70, 95% confidence interval = 1.36-2.13), male (odds ratio = 1.81, 95% confidence interval = [1.49, 2.20]), had increased alcohol use (odds ratio = 1.58, 95% confidence interval = [1.35, 1.86]), poor physical health (odds ratio = 1.62, 95% confidence interval = [1.36, 1.92]), increased income worries (odds ratio = 1.81, 95% confidence interval = [1.54, 2.12]) or prior mental illness (odds ratio = 3.27, 95% confidence interval = [2.80, 3.82]). Having dependent children was protective (odds ratio = 0.75, 95% confidence interval = [0.61, 0.92]). Fewer than half (388/819) of the healthcare workers who reported thoughts of suicide or self-harm sought professional support. Healthcare workers with thoughts of suicide or self-harm were more likely to seek support if they were younger (⩽30 years cf. >50 years; odds ratio = 1.78, 95% confidence interval = [1.13, 2.82]) or had prior mental health concerns (odds ratio = 4.47, 95% confidence interval = [3.25, 6.14]). Conclusion: One in 10 Australian healthcare workers reported thoughts of suicide or self-harm during the pandemic, with certain groups being more vulnerable. Most healthcare workers with thoughts of suicide or self-harm did not seek professional help. Strong and sustained action to protect the safety of healthcare workers, and provide meaningful support, is urgently needed.